Surgical management of ossification of the posterior longitudinal ligament in the cervical spine. (February 2020) - Cerecedo-Lopez, Christian D.; Tafel, Ian; Lak, Asad M.; Chi, John; Lu, Yi; Groff, Michael; Zaidi, Hasan A.
Highlights: OPLL is most common in Asia and estimated US prevalence is 0.7%. Early surgical decompression is recommended to prevent irreversible damage. Different types of OPLL are continuous, mixed, other and segmental. Positive K-line was found to be associated with a good functional outcome. Increased awareness of OPLL will hopefully improve clinical outcomes. Abstract: OPLL is a progressive process that can result in spinal cord compression and myelopathy. Various surgical approaches for the management of OPLL in the cervical spine exist. Our goal is to present our institution's experience in the management of OPLL over the last 20 years. Sixty-eight patients underwent surgery for cervical OPLL. Mean age at surgery was 56.9 years. No differences between demographic characteristics and surgical approach were identified. There were no significant differences between the approaches regarding the mean estimated blood loss, occurrence of durotomy, reoperation rate, positive K-line and preoperative cervical spine sagittal balance. Number of levels operated on was significantly different (anterior approach 2 ± 0.8 levels, posterior approach 4.3 ± 1.3 levels, combined approach 3.3 ± 0.9 levels, p-value <0.01), but postoperative sagittal balance was not (anterior approach Cobb angle 11.9 ± 5.8 degrees, posterior approach Cobb angle 7 ± 3.5 degrees, combined approach Cobb angle 16.7 ± 7.3 degrees, p-value = 0.09). Functional outcomes were good for 70% of patients and did not significantly differ across approaches (anterior approach 28%, posterior approach 33%, combined approach 9%, p-value = 0.46). Good functional outcomes were more commonly observed in patients with a positive K-line (OR 0.2, 95% CI 0.04–0.9, p-value 0.05) while poor outcomes were most commonly observed in patients with an occupational ratio >0.6 (OR 6.9, 95% CI 1.35–42.7, p-value 0.02). OPLL is a rare disease for which prompt referral for surgical decompression may lead to good clinical outcomes.